2002
DOI: 10.1093/nar/30.7.1563
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing loss and rescue of DNA binding upon single and double mutations in the p53 core domain

Abstract: The mutation of R273-->H in the p53 core domain (p53-CD) is one of the most common mutations found in human cancers. Although the 273H p53-CD retains the wild-type conformation and stability, it lacks sequence-specific DNA binding, a transactivation function and growth suppression. However, mutating T284-->R in the 273H p53-CD restores the DNA binding affinity, and transactivation and tumour suppressor functions. Since X-ray/NMR structures of DNA-free or DNA-bound mutant p53-CD molecules are unavailable, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…His residues in the biologically active state should be protonated. We selectively protonated five His residues according to the suggestion of Wright et al (28). The only two His residues left in the deprotonated state are His-179, which is coordinated to Zn, and His-214, which is close to R174.…”
Section: Surface Analysis Of the P53 Cbd: Identification Of Protein-pmentioning
confidence: 99%
“…His residues in the biologically active state should be protonated. We selectively protonated five His residues according to the suggestion of Wright et al (28). The only two His residues left in the deprotonated state are His-179, which is coordinated to Zn, and His-214, which is close to R174.…”
Section: Surface Analysis Of the P53 Cbd: Identification Of Protein-pmentioning
confidence: 99%
“…Although it was reported that the K120R mutant binds p53 target sites equally well as wt p53, this was only investigated for a limited number of target genes. 151 The K120 residue in p53, however, interacts with the major groove of DNA 170 and, therefore, possible phenotypes arising in putative K120R knock-in mice may not entirely be due to the effects on target gene expression caused by loss of p53 acetylation.…”
mentioning
confidence: 99%
“…MD simulations have been performed to study structural and dynamic properties of the p53, DNA binding domain [36][37][38]. Although, only few MD simulations on p53-DNA wild type complex and its mutational effects have been reported till date [36,39,40]. Free energy calculations through MD simulations are reported to identify loss and rescue of DNA binding to p53 core domain by single and double mutations [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Although, only few MD simulations on p53-DNA wild type complex and its mutational effects have been reported till date [36,39,40]. Free energy calculations through MD simulations are reported to identify loss and rescue of DNA binding to p53 core domain by single and double mutations [39,40]. One of the recent MD simulations on the p53 monomer, depicts a computational metric which helps to determine the functionality of a particular p53 mutant [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation